Technocoat Group (M) Sdn Bhd Go Or Not To Go - Lim, Cheng Seong (1999)
At around 7.30 pm. Mr Freddie Yan, Managing Director of Technocoat Group (M) Sdn Bhd (TGSB) was still in his office. Like usual, he sank into deep thought, but this time is different. "I need to make up my mind before next Friday," he told himself. Mr C. S. Gan, Executive Director, the owner of Box Matel Sdn Bhd had just called him again, he wanted to find out the decision on the expansion project of TGSB into the India market. Mr. Freddie Yan sat at his high back chair and look at the report prepared by his International Business Manager, Mr S. S. Leong. Regarding the alternative ways to penetration into India market. He recalled the responses of other directors and senior managers in the directors meeting few days ago. Mr K. H. Wong, Senior Technical Manager had high lighted that the company is expanding too fast for the existing man power. Especially skilled technical staff could not cope with the expansion. Mr. Eddy Ong had mentioned that, the administrating process and operation system was not functioned properly, only the accounting and finance system are good order as done by appointed accountant finn. Mr. Freddie Yan ponder upon the internal problems that been listed down by Mr. Ong, 20% rejection rate, delay in production, delivery problem, high expenses, conflict between head office and branches Mr. Freddie Yan was informed in the meeting that the problems occur since TGSB established its two overseas projects in Indonesia and Thailand about 1 year ago. TGSB had entered Indonesian market without any proper planning, and there were only slim profit return from Thailand's investment. These return from those investments are not up to the expectation of Mr. Freddie Van.